Fraud and corruption: prevention and detection - Iyer, Nigel (Gower, 2006)
The greatest unmanaged risk -- A corporate novel in three parts -- Fraud and corruption demystified -- Recognising and respecting the risk -- Fraud and corruption risk assessment -- Prevention and detection up front -- Managing incidents -- Resistance : the ultimate goal -- References -- Permissions -- Appendices